Secure provenance-based communication using visual encryption. (30th October 2019) - Kumar, Kukatlapalli Pradeep; Cherukuri, Ravindranath C.
Explicit specification of the historical record of an instance or a data item is called data provenance. It has many applications in various fields with regards to its importance on capturing data flow mechanisms. However, on the other hand, there are good number of security mechanisms in place to withstand the cyber-attacks. Almost all of these algorithms uses complex mathematical calculations in providing security for the systems. Visual cryptography is a peculiar approach which uses concept of secret sharing by dividing the message into transparencies as encryption process. Upon superimposing transparencies one obtains the original message. In this paper, we propose secret sharing as a notion of security onto data provenance. Main inference of this writing is to throw a model combining above two mentioned aspects which gives away an indigenous solution in the area of information security. This proposed model is implemented with specific use case scenarios for substantiation and related analysis. Simulated results and discussion of the same is presented in the paper.